Ceruloplasmin gene‐deficient mice with experimental autoimmune encephalomyelitis show attenuated early disease evolution. Issue 6 (27th January 2014) - Gresle, Melissa M.; Schulz, Katrin; Jonas, Anna; Perreau, Victoria M.; Cipriani, Tania; Baxter, Alan G.; Miranda‐Hernandez, Socorro; Field, Judith; Jokubaitis, Vilija G.; Cherny, Robert; Volitakis, Irene; David, Samuel; et al.
<x xml:space="preserve">Abstract</x> We conducted a microarray study to identify genes that are differentially regulated in the spinal cords of mice with the inflammatory disease experimental autoimmune encephalomyelitis (EAE) relative to healthy mice. In total 181 genes with at least a two‐fold increase in expression were identified, and most of these genes were associated with immune function. Unexpectedly, ceruloplasmin (Cp), a ferroxidase that converts toxic ferrous iron to its nontoxic ferric form and also promotes the efflux of iron from astrocytes in the CNS, was shown to be highly upregulated (13.2‐fold increase) in EAE spinal cord. Expression of Cp protein is known to be increased in several neurological conditions, but the role of Cp regulation in CNS autoimmune disease is not known. To investigate this, we induced EAE in Cp gene knockout, heterozygous, and wild‐type mice. Cp knockout mice were found to have slower disease evolution than wild‐type mice (EAE days 13–17; P = 0.05). Interestingly, Cp knockout mice also exhibited a significant increase in the number of astrocytes with reactive morphology in early EAE compared with wild‐type mice at the same stage of disease. CNS iron levels were not increased with EAE in these mice. Based on these observations, we propose that an increase in Cp expression could contribute to tissue damage in early EAE. In addition, endogenous CP either directly or indirectly inhibits astrocyte reactivity during early disease, which could also worsen early disease evolution. © 2014 Wiley Periodicals, Inc.